Cytokine balance and cytokine-driven natural killer cell dysfunction in systemic juvenile idiopathic arthritis. Issue 1 (February 2015) - Avau, Anneleen; Put, Karen; Wouters, Carine H.; Matthys, Patrick
Abstract: Systemic juvenile idiopathic arthritis (sJIA) is a severe inflammatory childhood disorder, characterized by a specific pattern of systemic features and a typical cytokine profile. Patients are at risk to develop macrophage activation syndrome (MAS), an acute life-threatening condition defined by excessive proliferation and activation of macrophages and T cells. Defects of unknown cause in the natural killer (NK) cell cytotoxic capacity are presumed to underlie the pathogenesis of MAS and have been detected in sJIA patients. Here, we provide an overview of the cytokine profiles in sJIA and related mouse models. We discuss the influence of cytokines on NK cell function, and hypothesize that NK cell dysfunction in sJIA is caused by altered cytokine profiles.